Mood state monitoring of training and recovery in elite kayakers - Kenttä, G.; Hassmen, P.; Raglin, J. S. (European Journal of Sport Science, 2006)
Eleven elite kayakers performed an identical weekly training schedule each week during a 3-week training-camp. The Profile of Mood States (POMS) inventory ("right now" instructions) was completed before and after selected workouts each week to assess both training-induced mood disturbances and the extent of recovery following short and long rest. The ratio of POMS vigour to POMS fatigue scores was used as an "energy index". Energy index scores were compared with ratings of perceived exertion (RPE) to address the size of the training load. Performance measures were obtained during the first and last week. The results showed that the energy index decreased (p<0.01) throughout the camp and did not return to initial values following either the short (one night) or long rest (two nights and one day). Performance measures and RPE remained unaffected throughout training, as did the POMS depression scores, indicating that the athletes experienced an overreached state but did not develop staleness. Our results suggest that repeated evaluation using POMS fatigue, vigour, and depression scores during periods of intensified training may help prevent athletes from becoming severely overreached and reduce the likelihood of staleness.